The Impact of Halal Certification on the Muslim Community’s Interest in Using Hotel Products - Jan, Radlyah Hasan (Tasharruf: Journal Economics and Business of Islam, 2024)
The purpose of this study is to investigate the impact of halal certification in hotels on Muslim communities' interest in picking accommodations. Halal certification ensures that the services and facilities provided fulfill Sharia criteria, such as cleanliness, halal food, and services that are compatible with Islamic ideals. In the context of halal tourism, which is expanding, the presence of halal-certified hotels is one of the key draws for Muslim tourists. This study employs a quantitative approach utilizing a survey method, in which data is acquired by sending questionnaires to respondents chosen using a purposive sampling strategy. Data was analyzed using statistical methods to determine the relationship between the existence of halal certification and the Muslim community's interest. In data analysis, several statistical tests are utilized, such as validity, reliability, normality, linearity tests, simple linear regression tests, t tests, and coefficient of determination tests. The study's findings indicate that halal certification has a substantial impact on the Muslim community's interests. The estimated t value of 11.696 with a significance of 0.001 <0.05 supports the acceptance of hypothesis H1. The coefficient of determination test had a 58.3% effect, while the remaining 41.7% was influenced by other variables, specifically promotion, price, and location, which were not explained in this study.